3D dynamic model of healthy and pathologic arteries for ultrasound technique evaluation - Balocco, Simone; Basset, Olivier; Azencot, Jacques; Tortoli, Piero; Cachard, Christian (Medical physics (Lancaster), 2008)
A 3D model reproducing the biomechanical behavior of human blood vessels is presented. The model, based on a multilayer geometry composed of right generalized cylinders, enables the representation of different vessel morphologies, including bifurcations, either healthy or affected by stenoses. Using a finite element approach, blood flow is simulated by considering a dynamic displacement of the scatterers (erythrocytes), while arterial pulsation due to the hydraulic pressure is taken into account through a fluid-structure interaction based on a wall model. Each region is acoustically characterized using FIELD II software, which produces the radio frequency echo signals corresponding to echographic scans. Three acoustic physiological phantoms of carotid arteries surrounded by elastic tissue are presented to illustrate the model’s capability. The first corresponds to a healthy blood vessel, the second includes a 50% stenosis, and the third represents a carotid bifurcation. Examples of M mode, B mode and color Doppler images derived from these phantoms are shown. Two examples of M -mode image segmentation and the identification of the atherosclerotic plaque boundaries on Doppler color images are reported. The model could be used as a tool for the preliminary evaluation of ultrasound signal processing and visualization techniques.